Temperature behaviour of ultrasound contrast agents - Mulvana, H; Eckersley, R; Stride, E (2009)
Accurate characterization of ultrasound contrast agents (USCAs) is of increasing importance as their use for quantitative imaging and therapeutic application is explored. In the laboratory, such investigations are frequently undertaken in a water bath at room temperature. The effect of temperature on single bubbles has previously been demonstrated [1]. However, the effect on the acoustic properties of bulk suspensions is not presented in the literature. The acoustic and physical properties of bulk SonoVue (Bracco, Milan) suspensions over a range of temperatures (20-45°C) are investigated. Attenuation and scattering both increased with temperature over the range 20-40°C, for example at an insonation pressure of 100 kPa, signal attenuation increased from 1.5 dB to 2.5 dB, and scattering by 2 dB. The frequency spectra of the attenuated signals revealed a decrease in the frequency of peak attenuation (fa) with increasing temperature, suggesting an increase in bubble diameter. Above 40°C, attenuation was again decreased, and fa increased, implying that bubbles increased to a critical diameter and were destroyed, resulting in a decrease in signal attenuation. This effect was most apparent at 45°C. Additionally, increasing temperature from 20 - 40°C was shown to affect bubble stability by influencing bubble dissolution. We show that the acoustic characteristics of the USCA SonoVue are significantly influenced by temperature. The results suggest that measurements made at room temperature require careful interpretation before conclusions can be drawn regarding contrast agent behaviour in vivo. ©2009 IEEE.